Step * 1 2 of Lemma rcos-seq-converges


1. ∀n:ℕ+((rcos-seq(n 1) rcos-seq(n)) ≤ ((r1/r(3164556962025316455)) (rcos-seq(n) rcos-seq(n 1))))
⊢ (r(3164556962025316455) (rcos-seq(1) rcos-seq(0))/r(3164556962025316455 1)) ≤ (r1/r(1000000000))
BY
Assert ⌜(r(3164556962025316455) (rcos-seq(1) rcos-seq(0))/r(3164556962025316455 1)) < (r1/r(1000000000))⌝⋅ }

1
.....assertion..... 
1. ∀n:ℕ+((rcos-seq(n 1) rcos-seq(n)) ≤ ((r1/r(3164556962025316455)) (rcos-seq(n) rcos-seq(n 1))))
⊢ (r(3164556962025316455) (rcos-seq(1) rcos-seq(0))/r(3164556962025316455 1)) < (r1/r(1000000000))

2
1. ∀n:ℕ+((rcos-seq(n 1) rcos-seq(n)) ≤ ((r1/r(3164556962025316455)) (rcos-seq(n) rcos-seq(n 1))))
2. (r(3164556962025316455) (rcos-seq(1) rcos-seq(0))/r(3164556962025316455 1)) < (r1/r(1000000000))
⊢ (r(3164556962025316455) (rcos-seq(1) rcos-seq(0))/r(3164556962025316455 1)) ≤ (r1/r(1000000000))


Latex:


Latex:

1.  \mforall{}n:\mBbbN{}\msupplus{}
          ((rcos-seq(n  +  1)  -  rcos-seq(n))  \mleq{}  ((r1/r(3164556962025316455))
          *  (rcos-seq(n)  -  rcos-seq(n  -  1))))
\mvdash{}  (r(3164556962025316455)  *  (rcos-seq(1)  -  rcos-seq(0))/r(3164556962025316455 
-  1))  \mleq{}  (r1/r(1000000000))


By


Latex:
Assert  \mkleeneopen{}(r(3164556962025316455)  *  (rcos-seq(1)  -  rcos-seq(0))/r(3164556962025316455 
                -  1))  <  (r1/r(1000000000))\mkleeneclose{}\mcdot{}




Home Index